1998
DOI: 10.1590/s1415-47571998000300019
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic correlations and correlated responses to selection in cashew (Anacardium occidentale L.)

Abstract: The present study estimates variances and genetic and phenotypic correlations for five traits in 27 progenies of cashew trees (Anacardium occidentale L.). Data were obtained from a trial conducted in 1992 at Pacajus, Ceará, experimental station of Embrapa Agroindústria Tropical. The characters studied were plant height (PH), North-South and East-West canopy spreads (NSS, EWS), and primary and secondary branch numbers (PBN, SBN). All genetic and phenotypic correlations presented positive and significant values.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
1
5
0
3
Order By: Relevance
“…above 10 years old) at the commencement of the phenotypic evaluation in 1999/2000. Based on the data from previous studies (Masawe, 1994;Azevedo et al, 1998;Aliyu, 2006;Aliyu & Awopetu 2007a), only ten yield-related component characters (whole fruit weight -WWT, individual nut weight -NWT, total nut yield per tree -NYT, kernel weight -KWT, number of hermaphrodite flowers per panicle -HPP, percentage of pollen fertility -PPS, tree canopy size -TCS, days to optimum flowering-DFF, days to optimum fruit maturity -DFM and effective harvesting period (day) -HPD were selected for the phenotypic evaluation. The ten years data (1999-2009) were statistically analyzed using SYSTAT version 13.0 softwares (Systat Software, Inc. USA) and compared thereafter with three years data (Aliyu & Awopetu, 2007a).…”
Section: Update On the Genetic Diversity Of The Nigerian Cashew Treesmentioning
confidence: 99%
“…above 10 years old) at the commencement of the phenotypic evaluation in 1999/2000. Based on the data from previous studies (Masawe, 1994;Azevedo et al, 1998;Aliyu, 2006;Aliyu & Awopetu 2007a), only ten yield-related component characters (whole fruit weight -WWT, individual nut weight -NWT, total nut yield per tree -NYT, kernel weight -KWT, number of hermaphrodite flowers per panicle -HPP, percentage of pollen fertility -PPS, tree canopy size -TCS, days to optimum flowering-DFF, days to optimum fruit maturity -DFM and effective harvesting period (day) -HPD were selected for the phenotypic evaluation. The ten years data (1999-2009) were statistically analyzed using SYSTAT version 13.0 softwares (Systat Software, Inc. USA) and compared thereafter with three years data (Aliyu & Awopetu, 2007a).…”
Section: Update On the Genetic Diversity Of The Nigerian Cashew Treesmentioning
confidence: 99%
“…However, such breeding methods require adequate information about the genetic variability of the crop species and relationships between yield-related traits. Although studies on the correlations between yield-related characters have been reported (Aliyu, 2006;Azevedo et al, 1998), unfortunately, those studies never accounted for the trade-off between the nut size and nut number that may be crucial to cashew tree yield. There have been contrasting reports in the literature on the seed size and number trade-off in plants.…”
Section: Introductionmentioning
confidence: 99%
“…O elevado coeficiente de variação para ramos secundários pode ter ocorrido por serem plantas jovens, fato que também foi verificado por Azevedo et al(1998) em plantas com coeficiente de variação de 23,19 na idade de 16 meses. O cajueiro-anão é uma planta que apresenta um coeficiente de variação elevado, contudo, o encontrado para esta variável pode ser considerado dentro dos limites aceitáveis para a experimentação (Barros et al, 2000).…”
Section: Resultsunclassified
“…Com a determinação do coeficiente de correlação entre as variáveis, foi constatada uma tendência de influência positiva das variáveis: altura da copa, diâmetro do caule, ramos primários e secundários, estimativa da cobertura do dossel e envergadura da copa, e uma tendência de influência negativa da relação altura de copa e diâmetro do caule (Tabela 6). Azevedo et al (1998), avaliando progênies de cajueiro anão, através dos caracteres altura da planta, direções norte-sul e leste-oeste, ramos primários e secundários, encontraram correlação positiva e significativa em todas as variáveis. Portanto, aumentando ou reduzindo a média de qualquer um dos caracteres, pode-se afetar indiretamente a média dos outros.…”
Section: Table 4 Means Of Nineteen Progenies For Plant Height (Ap) (unclassified